(untitled) (Entrepreneurship Journal for Finance and Business, 2022)
The research aims to identify the role of the information management environment in enhancing the knowledge management strategy. The research relied on the descriptive and analytical approach to complete the requirements of his philosophy, and the General Directorate of Education of Kirkuk was chosen as a community to implement the research through the individuals working in it. The research sample consisted of (40) respondents and the questionnaire was used as a A main tool for data collection, the analysis of these data was conducted using the (SPSS-V24) program, and the research reached a set of conclusions, the most important of which (there is a correlation and impact relationship for the information management environment and the knowledge management strategy at the micro and macro levels), and based on the conclusions reached, a presentation was made A set of proposals, the most important of which is (the need for the research sample organization to seek to employ information technology as a tool for managing the relationships between its units and managing the relationships between the organization itself and the relevant external parties).